Pengembangan Lembar Self-Assessment untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SMP melalui Pendekatan Saintifik - Ismi Amalia Sari; Yusrizal Yusrizal; M. Duskri (Universitas Syiah Kuala, 2018)
Students ability to solve mathematics problems, especially problem-solving questions, is still relatively low despite the 2013 curriculum requiring students to be able to solve such questions and expecting the learning process to apply a scientific approach. This learning process requires students to be more engaged and teachers to facilitate students experiencing difficulties during the learning process. However, teachers have a little knowledge of the difficulties experienced by students in the learning process because the learning process conducted in the classroom does not provide enough information concerning the students difficulties. Students self-assessment can help students in identifying their difficulties, and the teacher can choose the right strategies to overcome them. Therefore, it is necessary to develop learning instruments encouraging students to engage more in assessing their abilities which in turn improving their problem-solving abilities.This study aimed to develop and produce the valid, practical and effective self-assessment sheet and student worksheet to improve students problem-solving skills employing scientific approach. This study was development research referring to the Dick and Carey model. The learning instruments trials were conducted at one of the junior high schools in Banda Aceh. The results of the study found that the self-assessment sheet and student worksheet employing the scientific approach satisfied the criteria of being valid, practical and effective. Thus, teachers and students can use this self-assessment sheet and worksheet to improve the quality of learning in schools.